Computer Assisted Learning for Enhancing Mastery of Concepts in Science - Onditi, Sharon Anyango; Ajwang, Stephen Oloo (Universitas Terbuka, 2020)
This study examined the effects of Computer Assisted Learning (CAL) on the mastery of Science concepts by learners in universities. Teaching and learning of Science concepts present learners with numerous challenges. Of critical concern is the negative perception by learners that Science based subjects are difficult, thus contributing to widespread poor performance by the learners in the national examinations and subsequently poor choice of the subject in the universities. Solomon Four Group experimental design was employed for the study. The target population comprised all first-year students taking science subjects in 8 universities in western Kenya. A sample size of 335 students was determined using Krejcie & Morgan table (1970). The universities were divided into two forming experimental and control groups.Ã‚Â Ã‚Â The study was carried out in 4 months spanning 16 weeks where pretest was administered after the first 8 weeks of conventional teaching and post-test administered after the next 8 weeks of treatment. Pretest and post-test Science Achievements Test (SAT) on two topics, digestive system and light and optics, were designed and administered by the respective lecturers, and scores recorded. Piloting was carried before the use of the instruments, and a reliability coefficient of 0.85 on SAT was recorded.Ã‚Â Ã‚Â Data were analyzed using t-test one-way ANOVA. The study found that 171 students taught using CAL achieved significantly higher scores in SAT compared to164 students taught through conventional methods with a mean gain of 2.851. The study demonstrated that CAL enhanced active manipulation of content and promoted interaction with content, and gave reality to abstraction. The study may be significant to educationists, lecturers, researchers, and policy makers as it provides insight on the benefits of applying Computer Assisted Learning in Science Education.Ã‚Â